Antimicrobial consumption and resistance in a tertiary care hospital in Brazil: a 7-year time series - Amanda F Medeiros; Caryne M Bertollo; Bárbara CD Faria; Claudmeire DC Almeida; Edna MM Leite; Laura R Vieira; Ana FF Souza; Mauro HNG Abreu; Renan P Souza; Maria AP Martins (Journal of Infection in Developing Countries)
Introduction: Antimicrobial resistance (AMR) is a major public health challenge globally. This study aimed to analyze the antibacterial consumption (ATBc), and the incidence of multidrug-resistant organisms (MDRO), focusing on pathogens Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp. (ESKAPE group), in a Brazilian tertiary care hospital.